Implementasi Media Audio Visual Untuk Mengembangkan Kecerdasan Bahasa Anak Usia 5-6 Tahun di TK Pembina Desa Sungai Paduan Kecamatan Teluk Batang Kabupaten Kayong Utara - Sajidin, Hendra Saputrawan; Halida; Annisa Amalia (Program Studi Pendidikan Guru PAUD FKIP Universitas Mulawarman, 2025)
The purpose of this study was to develop the language intelligence of children aged 5-6 years in the Pembina Kindergarten of Sungai Paduan Village, Teluk Batang District, North Kayong Regency. Based on the above background, the researcher is interested in conducting a class actionresearch with the title ‘Implementation of AudioVisual Learning Media to Develop the Language Intelligence of 5-6 YearOld Children at Kindergarten Pembina Sungai paduan Village’ which was conducted on 27 May 2024 to 15 July 2024. This class action research was motivated by the following: (1) The application of audio-visual learning media has a significant effect on the development of children's language intelligence at the Pembina Kindergarten. (2) The results of observations and analysis of existing data, it can be seen that there is a development of the ability to apply audio-visual media to develop language intelligence. (3) The development of language intelligence can be improved by using audio visual media in group B kindergarten, and can also be used as a reference for further research.